2011
DOI: 10.1111/j.1462-5822.2011.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Pore-forming toxins induce multiple cellular responses promoting survival

Abstract: SummaryPore-forming toxins (PFTs) are secreted proteins that contribute to the virulence of a great variety of bacterial pathogens. They inflict one of the more disastrous damages a target cell can be exposed to: disruption of plasma membrane integrity. Since this is an ancient form of attack, which bares similarities to mechanical membrane damage, cells have evolved response pathways to these perturbations. Here, it is reported that PFTs trigger very diverse yet specific response pathways. Many are triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
272
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(282 citation statements)
references
References 65 publications
7
272
2
Order By: Relevance
“…A possible reason for this failure to repair EqtII-induced membrane injuries could be related to the small size of the pores induced. Similarly to EqtII, ␣-toxin or aerolysin form pores with ϳ2-nm diameter, and cells treated with these toxins had more difficulties or were unable to recover (38). However, the nature of the cell survival mechanisms in response to the attack of PFPs is still poorly understood.…”
Section: Equinatoxin II Binds Quickly To the Plasma Membrane Andmentioning
confidence: 99%
“…A possible reason for this failure to repair EqtII-induced membrane injuries could be related to the small size of the pores induced. Similarly to EqtII, ␣-toxin or aerolysin form pores with ϳ2-nm diameter, and cells treated with these toxins had more difficulties or were unable to recover (38). However, the nature of the cell survival mechanisms in response to the attack of PFPs is still poorly understood.…”
Section: Equinatoxin II Binds Quickly To the Plasma Membrane Andmentioning
confidence: 99%
“…Using this methodology, the intracellular kinase proteins activated as a consequence of pore formation by StII have been elucidated . Employing 46 antibodies against 29 different kinases, it was observed that the phosphorylation of MAP kinases p38 and ERK was similar to what has been described for other PFT, such as streptolysin O, pneumolysin O, anthrolysin O, Cry5B, aerolysin and LLO (Ratner et al 2006;Aguilar et al 2009;Porta et al 2011;Gonzalez et al 2011).…”
Section: Interaction With Nucleated Cellsmentioning
confidence: 84%
“…Strikingly, it has been found that membrane recovery upon StII damage takes place in a time scale similar to that upon LLO damage even though these two PFT form pores that differ greatly in size. In addition, for StII, membrane recovery occurs in a completely different time span to that observed for other bacterial PFT also producing small pores (Husmann et al 2009;Gonzalez et al 2011). At sub-lytic concentrations (100 ng/ml) in BHK cells, StII is able to cause a drop of intracellular potassium (<40%) after 20 min of incubation.…”
Section: Interaction With Nucleated Cellsmentioning
confidence: 95%
See 2 more Smart Citations